SALIENT FEATURES OF CIRCULATING RESPIRATORY VIRUSES IN THE PRE– AND PANDEMIC INFLUENZA AND COVID–19 SEASONS - I. V. Kiseleva (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
Abstract. A wide variety of zoonotic viruses that can cross the interspecies barrier promote the emergence of new, potentially pandemic viruses in the human population that was often accompanied by the disappearance of existing circulating strains. Among the various reasons underlying this phenomenon is the strengthening of populational immunity by expanding the immune layer of the population and improving the means and methods of medical care. However, “Natura abhorret vacuum”, and new pathogens come to replace disappearing pathogens. In the past ten years, there have been two critical events – the pandemic spread of the swine influenza A (H1N1) pdm09 virus in 2009 and the novel SARS–CoV–2 coronavirus in 2019, providing scientists with a unique opportunity to learn more about a relationship between respiratory viruses and their pathogenesis. Together with viruses of pandemic significance, a large number of seasonal respiratory viruses circulate, which contribute to the structure of human morbidity, and co–infections aggravate the condition of the illness. In the conditions of the spread of new viruses with unexplored characteristics, in the absence of means of prevention and therapy, it is especially important to prevent the aggravation of morbidity due to mixed infections. Here we review the mutual involvement of pandemic influenza A(H1N1)pdm09 and SARS–CoV–2 coronavirus and seasonal respiratory viruses in the epidemic process, discuss some issues related to their spread, potential causes affecting the spread and severity of the morbidity. The given facts, testify to the existence of seasonality and temporal patterns of the beginning and end of the circulation of respiratory viruses. Interestingly, the beginning of the circulation of the pandemic influenza A(H1N1)pdm09 virus led to a shift in the timing and intensity of circulation of some respiratory viruses, which is probably caused by the existence of "replication conflicts" between them, and did not affect others. Co–infection with SARS–CoV–2–19 and other respiratory viruses, especially respiratory syncytial virus and rhinoviruses, was quite often observed. At the current stage, no aggravating effect of influenza on the course of COVID–19 in mixed infection has been established. Whether this is due to the mild course of influenza infection in the 2020 epidemic season, or the competitive impact of SARS–CoV–2 on influenza viruses is not yet clear. Experts are still at the stage of accumulating facts and working on creating means of effective prevention and treatment of the new coronavirus infection.